HYGIENIC RECOMMENDATIONS FOR THE PREVENTION OF SCHOOL MYOPIA AND OTHER VISUAL IMPAIRMENTS IN CHILDREN OF PRIMARY SCHOOL AGE (American Journal of Interdisciplinary Research and Development, 2022)
In childhood, especially during school years, myopia (myopia) is most common, which can be congenital and acquired. Features of the occurrence of congenital myopia lead to malformations of the eyeball, and if this is combined with weakness of the sclera, then it progresses. It is known that the number of myopic children is growing as students move from elementary to middle and senior classes. The number of myopic people especially increases, starting from 11-14 years. At the age of 19-25 years, the share of ee reaches 28.7% (Golovanova T.P. Organization of assistance to children with refractive errors in school conditions - Bulletin of Ophthalmology. - 2005. - No. 2. - P. 3-5).